IMMUNE SYSTEM AND BACTERIAL INFECTION MODEL - Nastinov Sadriddin Tojiddin o‘g‘li (Web of Journals Publishing, 2025)
This article studies the interaction between the human immune system and bacterial infections based on mathematical modeling. The cellular and molecular stages of the immune response, as well as bacterial proliferation, toxin release, and interaction with the immune system are taken into account in the model. The study aims to simulate various scenarios of infection based on mathematical equations and identify key factors in the restoration of health.
Keywords: Immune system. Bacterial infection. Mathematical modeling. Immune response. Neutrophils. Macrophages. T-lymphocytes. Antibody. Infection dynamics. Pathogen–immune system interaction. Ordinary differential equations (ODE). Infection model. Coinfection. Antibiotic resistance. Immunotherapy. Simulation and prediction.